Bureaucratic Reform Strategy Employee Performance in the Secretariat of DPRD Kepulauan Riau Province - Fitri Kurnianingsih; Nazaki Nazaki; Oksep Adhayanto (Jayapangus Press, 2021)
Bureaucratic reform is part of the organization's strategy to improve the quality of the organization's performance. The purpose of this research is to analyze the bureaucratic reform strategy in the Secretariat of the Regional House of Representatives (DPRD) of Kepulauan Riau Province on performance during the COVID-19 pandemic. The method used is descriptive qualitative, where the researcher makes observations according to the phenomena that exist within Kepulauan Riau Provincial DPRD Secretariat. Then the data analysis technique uses a logical model in accordance with the concept of performance which is part of bureaucratic reform. The results show that there is a weakening of the supporting factors in public services so that there is a weakening of organizational performance in facilities that are part of the supporting factors for Kepulauan Riau Provincial DPRD Secretariat due to the COVID-19 pandemic, besides that in the bureaucratic reform strategy, preparation and anticipation are needed in involving stakeholders if the involvement of other parties is considered necessary to encourage the improvement of the performance quality of the DPRD Secretariat of Kepulauan Riau Province.